Associação paraibana pelo progresso feminino: as contribuições educacionais para a mulher paraibana (1933 a 1939) - Fragoso, Verônica de Souza (2011)
The objective of this research is a priority, noting the contributions of the Association for the Advancement Paraibana Male - Female Page (AAPM) through, conveved in The Union newspapeer, training and access for women, especially Paraiba, greater education and social inclusion, in meaningful time of the decade from 1933 to 1939. By this premise, I propose also to understand the forms used by the same contributions to the feminist movement in Paraiba, identifying the reasons historical, political, economic, social, ideological, generating their views on education needs of women, besides identify the transformations in the educational thought of the entity in the course of its existence an dreve al the limits and possibilities that characterized this space in the Union newspaper, as the issues addressed and their relation to the context. This space was named Female Page conquered and managed by women who formed the Association for progress Paraibana Female (APPF), cell Male Brazilian Federation of Female Progress, headed by Bertha Lutz. In addition to articulate to the union of women from different social classes in winning the vote, granted in 1932, these women founded in 1933, the APPF and utilize the space in the Lades Home dissemination of his ideas, and equip your items in order to released the female society of that time the need to educate themselves to a full exercise of their rights.